S48 Inefficient ventriculo-arterial coupling contributes to reduced exercise capacity in pulmonary hypertension. (14th November 2013) - McCabe, C; Hoole,; White, P; Axell, R; Shapiro, L; Pepke-Zaba, J
Abstract : Introduction: Ventriculo-arterial (VA) coupling (Ees/Ea) in the right heart is defined by RV end-systolic elastance (Ees) and pulmonary arterial effective elastance (Ea) with Ees/Ea representing the mechanical efficiency of forward flow from the RV. Ees/Ea may influence exercise capacity in pulmonary hypertension (PH) because patients exhibit cardiac limitation at peak oxygen uptake (peak VO2 ) and suffer impaired exercise cardiac output adaptation. We hypothesised that Ees/Ea in the RV represents a physiological index of myocardial reserve and thus at inefficient ratios, may predispose to reduced exercise capacity. Methods: Using RV conductance catheterisation and contemporaneous incremental cardiopulmonary exercise testing, we evaluated Ees/Ea against peak VO2 in twenty patients with pulmonary vascular disease. Ees/Ea was compared with haemodynamic predictors of exercise capacity obtained from standard right heart catheterisation. Results: Resting Ees/Ea, absolute peak VO2 and predicted peak VO2 were 0.86 ± 0.40, 19.6 ± 6.7ml/Kg/min and 88 ± 23% respectively. Univariable predictors of absolute peak VO2 were patient gender, NYHA class, mean right atrial pressure, mean pulmonary artery pressure, cardiac index, conductance RV stroke volume and Ees/Ea (all p < 0.10). On bivariate analysis, the predictive value of Ees/Ea improved following adjustment for RV stroke volume (p = 0.03) but not for mean RA pressure (p = 0.21). Only Ees/Ea related linearly to percent predicted VO2 (R 2 = 0.32, p = 0.01). RV diastolic decay (-dP/dtmin )showed good correlation with O2 pulse evolution (r = 0.62, p < 0.01) although no single haemodynamic parameter differentiated absolute peak VO2 above and below its median value. Discussion: VA coupling is a marker of RV energetic efficiency and adds to the debate on the multifactorial determinants of exercise capacity in PH. Ees/Ea was comparable to other predictive haemodynamic parameters of exercise capacity and may represent the 'recruitable' myocardial reserve, important for maintaining cardiac output at increased metabolic demand. Ees/Ea may be a potential therapeutic target given the unclear relationship between pulmonary haemodynamics and patient symptoms.